(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
The unsuccessful exclusive breastfeeding must be avoided during a pandemic, because breast-milk can increase immunity for both mother and baby. The Pusat Damai public health center data shows that there is a decrease in the exclusive breastfeeding trend in 5 villages, namely in the Damai Center village by 69.2%, Gunam village by 80.0%, Dosan village by 87.0%, Marita village 87.0%, and Suka Gerundi village 88.9%. This study aims to determine the failure factors of exclusive breastfeeding in working mothers (a study of the Pusat Damai village, Sanggau district, West Kalimantan). This study used a case control design. The population in the study was 94 respondents. The research sample was 46 respondents (23 cases and 23 controls) who were taken by purposive sampling technique, using the chi square test with a confidence level of 95%. The results showed that there was a significant relationship between husband’s support and the failure of exclusive breastfeeding to working mothers (p value = 0.003), distance traveled (p-value = 0,000), travel time (p-value = 0,000), availability of place / breastfeeding facilities (p-value = 0.015), family trust (p-value = 0.030), mother’s perceptions about formula milk (p-value = 0.002). Therefore, recommendation for health workers in the work area of ​​the Pusat Damai public health center e.i. increasing information through counseling, educating about the importance of exclusive breastfeeding for babies, approaching families / husbands to support mothers in exclusive breastfeeding, advising mothers to provide stocks of breastmilk before mother left for work.